2004
DOI: 10.1023/b:bege.0000017872.25069.44
|View full text |Cite
|
Sign up to set email alerts
|

QTL Analysis of Multiple Behavioral Measures of Anxiety in Mice

Abstract: In a test battery consisting of an open-field arena, a light-dark box, a mirror-chamber box, an elevated plus maze, and an elevated square maze, 1,671 mice were tested, generating over 100 putative measures of anxiety in rodents. Quantitative trait loci (QTL) analysis was carried out on all measures, plus composite measures and phenotypic factor scores. Significant LOD scores were found for QTL on 17 chromosomes, with large and consistent QTL behavioral effects on chromosomes 1, 4, 7, 8, 14, 15, l8, and X. QTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
163
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(177 citation statements)
references
References 44 publications
12
163
2
Order By: Relevance
“…Finally, different genetic regions have been associated with specific mood and anxiety traits in both mice (Henderson et al, 2004), and humans (Foley et al, 2003;Jang et al, 2004), which can affect genetic association study results (Lotrich, 2011). Consistent with this, we have found that polymorphisms affecting TNF-a and IL-28b are associated with specific mood-related symptom clusters in individuals receiving IFN-a (Lotrich et al, 2010;Lotrich et al, 2011).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Finally, different genetic regions have been associated with specific mood and anxiety traits in both mice (Henderson et al, 2004), and humans (Foley et al, 2003;Jang et al, 2004), which can affect genetic association study results (Lotrich, 2011). Consistent with this, we have found that polymorphisms affecting TNF-a and IL-28b are associated with specific mood-related symptom clusters in individuals receiving IFN-a (Lotrich et al, 2010;Lotrich et al, 2011).…”
Section: Introductionsupporting
confidence: 83%
“…In fact, different specific depression symptoms may be influenced by different genes (Jang et al, 2004), a phenomenon long noted in mice where different chromosomal regions are implicated in anxiety-depending on what behavioral test is used (Henderson et al, 2004). The possibility that the Met allele is only associated with risk for a subset of symptoms may be one plausible reason that some studies do not replicate an association between depression risk and the BDNF Val/Met polymorphism Figueira et al, 2010;Middeldorp et al, 2010;Ribeiro et al, 2007;Suchanek et al, 2011;Wray et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We also show that the maternal 5-HT 1A R genotype, in combination with the offspring 5-HT 1A R genotype, results in reduced safe-area activity in the EPM. It has been shown previously that some of the QTLs in mice for threatening-and safe-area locomotor activity overlap (12). Nevertheless, the maternal 5-HT 1A R genotype alone was not sufficient to elicit a change in this measure.…”
Section: Discussionmentioning
confidence: 78%
“…Open field (OF) is another test of anxiety-like behavior, and, as in the EPM, reduced time spent and distance traveled in the center area of the field is indicative of an anxiety-like phenotype (7). However the OF is considered less stressful than the EPM (11), and quantitative trait locus (QTL) studies identified both shared and OF-specific loci (12). Anxiety in the OF was completely offspring-genotype dependent, and neither the post-nor the prenatal maternal environment, and not even their combination, increased anxiety ( Fig.…”
Section: Wt Offspring Of Heterozygote 5-ht 1a R-deficient Mothers Exhmentioning
confidence: 99%
“…The degree of avoidance of the open arms of the maze is considered a measure of the genetic predisposition, that is, trait anxiety, and is predictive of behavior in other tests of anxiety (Henderson et al, 2004;Trullas and Skolnick, 1993).…”
Section: Elevated Plus Mazementioning
confidence: 99%